Neuropeptide S Attenuates the Alarm Pheromone-Evoked Defensive and Risk Assessment Behaviors Through Activation of Cognate Receptor-Expressing Neurons in the Posterior Medial Amygdala - Shao, Yu-Feng; Wang, Can; Rao, Xiao-Ping; Wang, Hua-Dong; Ren, Yan-Li; Li, Jing; Dong, Chao-Yu; Xie, Jun-Fan; Yang, Xing-Wen; Xu, Fu-Qiang; Hou, Yi-Ping (Frontiers in Molecular Neuroscience, 2021)
Neuropeptide S (NPS) acts by activating its cognate receptor (NPSR). High level expression of NPSR in the posterior medial amygdala suggests that NPS-NPSR system should be involved in regulation of social behaviors induced by social pheromones. The present study was undertaken to investigate the effects of central administration of NPS or with NPSR antagonist on the alarm pheromone (AP)-evoked defensive and risk assessment behaviors in mice. Furthermore, H129-H8, a novel high-brightness anterograde multiple trans-synaptic virus, c-Fos and NPSR immunostaining were employed to reveal the involved neurocircuits and targets of NPS action. The mice exposed to AP displayed an enhancement in defensive and risk assessment behaviors. NPS (0.1–1 nmol) intracerebroventricular (i.c.v.) injection significantly attenuated the AP-evoked defensive and risk assessment behaviors. NPSR antagonist [D-Val5]NPS at the dose of 40 nmol completely blocked the effect of 0.5 nmol of NPS which showed the best effective among dose range. The H129-H8-labeled neurons were observed in the bilateral posterodorsal medial amygdala (MePD) and posteroventral medial amygdala (MePV) 72 hours after the virus injection into the unilateral olfactory bulb (OB), suggesting that the MePD and MePV receive olfactory information inputs from the OB. The percentage of H129-H8-labeled neurons that also express NPSR were 90.27 ± 3.56% and 91.67 ± 2.46% in the MePD and MePV, respectively. NPS (0.5 nmol, i.c.v.) remarkably increased the number of Fos immunoreactive (-ir) neurons in the MePD and MePV, and the majority of NPS-induced Fos-ir neurons also expressed NPSR. The behavior characteristic of NPS or with [D-Val5]NPS can be better replicated in MePD/MePV local injection within lower dose. The present findings demonstrated that NPS, via selective activation of the neurons bearing NPSR in the posterior medial amygdala, attenuates the AP-evoked defensive and risk assessment behaviors in mice.